2023
DOI: 10.3389/fchem.2023.1137547
|View full text |Cite
|
Sign up to set email alerts
|

Toad venom-derived bufadienolides and their therapeutic application in prostate cancers: Current status and future directions

Abstract: Cancer is the second leading cause of death worldwide. Specially, the high incidence rate and prevalence of drug resistance have rendered prostate cancer (PCa) a great threat to men’s health. Novel modalities with different structures or mechanisms are in urgent need to overcome these two challenges. Traditional Chinese medicine toad venom-derived agents (TVAs) have shown to possess versatile bioactivities in treating certain diseases including PCa. In this work, we attempted to have an overview of bufadienoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…Toad venom, known as Venenum bufonis, has been utilized for therapeutic purposes for many centuries in modern China as well as other Asian nations including South Korea and Japan, following it being appropriately dried and formulated [1,2]. Toad venom plays a central role as the primary constituent in various therapeutic formulations or Chinese patent medicines [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toad venom, known as Venenum bufonis, has been utilized for therapeutic purposes for many centuries in modern China as well as other Asian nations including South Korea and Japan, following it being appropriately dried and formulated [1,2]. Toad venom plays a central role as the primary constituent in various therapeutic formulations or Chinese patent medicines [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (400 MHz) and13 C NMR (100 MHz) data for compounds 1 and 2 in CD3OD a . Position 1 2 δC δH (J in Hz) δC δ H (J in Hz) 1 24.9, CH2 1.82 a , 1.42 a 24.7, CH2 1.80 a , 1.46 a 2 25.7, CH2 1.68 a 27.5, CH2 1.82 a , 1.26 a 3 72.1, CH 5.05, br s 67.1, CH 4.06, (br.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is prepared from the dried white secretion of the auricular glands and the skin glands of Bufo gargarizans Cantor or Bufo melanostictus Schneider [ 3 ]. According to the theory of traditional Chinese medicine, it has efficacy in providing detoxification, pain relief, resuscitation, and refreshment [ 4 , 5 ]. The chemical constituents of toad venom mainly include bufadienolides, indole alkaloids, sterols, polysaccharides, amino acids, and organic acids, among which bufadienolides and indole alkaloids are considered to be the main active ingredients [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical constituents of toad venom mainly include bufadienolides, indole alkaloids, sterols, polysaccharides, amino acids, and organic acids, among which bufadienolides and indole alkaloids are considered to be the main active ingredients [ 6 8 ]. Modern pharmacological studies have demonstrated that toad venom possesses a multitude of pharmacological activities, including antitumor, cardiac, antibacterial, and analgesic activities effects [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%